Supine Versus Prone Percutaneous Nephrolithotomy : An Early Experience - Uddin, Mohammad Nasir; Monwarul Karim, Kazi Mohammed; Ahmedullah, - (IAHS Medical Journal, 2022)
Background : Percutaneous Nephrolithotomy (PCNL) is a minimally invasive procedure and the gold standard for kidney stone larger than 2cm. Since it was first introduced PCNL has been carried out in the prone position. In 1987, Valdivia Uria became the first to introduce PCNL in supine position. Since then, many researchers have compared the superiority of supine of PCNL with traditional prone PCNL. We aimed to compare the surgical outcomes of supine versus prone PCNL in private hospital. Materials and methods: This study was a retrospective study conducted in Chattagram Metropolitan Hospital from January 2000 to February 2021. Total 52 patients underwent PCNL, in which 26 were performed in supine position and 26 performed using prone position. All data of both procedures were collected and statistically analyzed to compare between both groups. Results: In demographic characteristics of both groups male was predominate (69.2 vs 57.7). Both the groups were similar in terms of stone characteristics. There was no significant statistical difference in mean operative time ( 61.34 min vs 80.58min) blood transfusion ( 46.2% vs 53.8) stone clearance (96.2% vs 100%) and hospital stay ( 1-2 day vs 1-2). No major complications were observed. Conclusion: Although there was no significant difference of outcomes between two groups, PCNL in supine position is safe and it offers potential advantages of better ureteral access, patient handling, simultaneous retrograde and antegrade access, dependent track, easier air way control by anaesthesiologist. IAHS Medical Journal Vol 4(1), June 2021; 38-42